Vulvovaginitis in children and teens: relevance of clinical diagnosis - Vera Maria Fidalgo Nacif; Israel Figueiredo Júnior; Renato de Souza Bravo; Gesmar Volga Haddad Herdy (DST, 2013)
Introduction: Vaginal discharge is the most frequent complaint in Gynecology at any age. Pediatric and Adolescent Gynecology has specific features that differentiate it from gynecological care of women from other age groups. The search for a doctor, for children and adolescents, is generally accompanied by concern of parents and guardians. Objective: To evaluate the relevance of the clinical diagnosis face to the complaints suggestive of vulvovaginitis in children and adolescents. To identify symptoms, diagnoses, treatments, and outcomes in the study population. Subjects and Methods: Children and adolescents up to the of age of 15 years were selected for this retrospective study. They were looked after at the Pediatric and Adolescent Gynecology Ambulatory of the Hospital Universitário Antonio Pedro from 01/01/2002 to 31/12/2012. The following variables were studied: the city of origin of the patients, the way they were routed, age, status with or without menarche, complaints, while complaints, co morbidities, diagnosis, treatments performed, and outcome. Nonparametric test was used to verify the hypotheses established for the continuous variables. Results: From the pool of 203 patients included in the study, 46 had lack of hygiene care; 76, inappropriate clothing habits; 67, both; 11 patients were diagnosed with candidiasis; one was a carrier of the coalescence of the labia minora, and only two showed, vulvovaginitis. Conclusions: The relevance of the clinical diagnosis was proved, face to the complaints suggestive of vulvovaginitis, as 93.1 % of the study group did not show any kind of pathology.